Enforceability and suspension of administrative act in Spanish Administrative law: special reference to sanctioning acts - Rodríguez-Arana, Jaime (2020)
This study addresses the problem of the enforceability of administrative proceedings when dealing with disciplinary action. Constitutional principles and effective judicial protection govern this precept of administrative action so that such enforceability can always be subject to judicial control that prevents irreversible legal situations from occurring.